The venous drainage of the heart in porcupines (Hystrix cristata) - Atalar, Ö; Yilmaz, S; Dinç, G; Özdemir, D (Blackwell Verlag Gmbh, 2004)
The venous drainage of the heart in porcupines (Hystrix cristata) was investigated. Each of the five adult porcupines (three males, two females) was injected with a coloured latex mixture via the V. cava caudalis for the demonstration of the cardiac veins. The dissection of the specimens revealed that the venous drainage of the heart in porcupines was made by the V. cordis magna, V. distalis ventriculi sinistri, V. proximalis ventriculi sinistri, V. cordis caudalis (the left marginal vein), V. cordis media and Vv. cordis dextrae. The cardiac veins were observed in a subepicardial course on the heart except for the R. interventricularis paraconalis. The R. interventricularis paraconalis showed an intramyocardial course until the middle of the sulcus interventricularis paraconalis, and a subepicardial course after this point. The V. cordis magna and V. distalis ventriculi sinistri opened to the sinus coronarius. The V. cordis caudalis and the V. cordis media drained into the V. cava caudalis. The venous drainage of the conus arteriosus was made by the left V. coni arteriosi opening to the R. interventricularis paraconalis, and by the right V. coni arteriosi which continued to the Vv. cordis dextrae.